Assessing central bank commitment to inflation targeting: Evidence from financial market expectations in India - Vaishali Garga; Aeimit Lakdawala; Rajeswari Sengupta (Federal Reserve Bank of Boston, 2022)
We propose a novel framework to gauge the credibility of central banks' commitment to an inflation-targeting regime. Our framework combines survey data on macroeconomic forecasts with high-frequency financial market data to understand how inflation targeting makes economic agents change their perception about central bank decisions. Specifically, using the Reserve Bank of India's adoption of inflation targeting in 2015 as a laboratory, we apply two different approaches to estimate a market-perceived monetary policy rule and analyze how it changed with the implementation of inflation targeting. Both approaches indicate that the market perceived a larger response to inflation in the monetary policy reaction function following the adoption of inflation targeting. This evidence suggests that the market viewed the shift to inflation targeting as a credible commitment by the Reserve Bank of India.
Keywords: E44; E47; E52; E58; 330; macroeconomic forecasts; financial markets; credibility; inflation targeting; inflation expectations